Analysis of Mathematical Problem-Solving Ability on The Pythagoras’ Theorem - Suci Indah Sari; Zawahir Nafisah; Rohani Damayanti Sihotang; Annisaul Fadilah; Dwi Novita Sari (Riemann: Research of Mathematics and Mathematics Education, 2024)
Since mastery of problem-solving techniques is one of the main objectives of studying mathematics, such techniques are very important in the field of mathematical education. With the help of the Pythagorean theorem, the problem-solving skills of eighth-grade students will be assessed. SM Muhammadiyah 01 Field, Class VIII-1 Integrated Facilities, is the location of this research. This research uses qualitative research methodology. The instruments used in this study are four and ten-question model questionnaires labeled Highly Agree (SS), Agreed (S), and Disagreement (TS). This research resulted in high categories whose presentation scores reached 57 to 60 were obtained by 2 students, a medium category where its presentation ratings reached 35 to 46 was achieved by 21 students, and a low category where the presentation value reached 2 compared to 31 was achieved by 5 students.